Implementations Of Eco-Literacy in English Language Teaching for Smart Society Era: A Critical Review - Putri Indah Pratiwi; Desyrianti Ramadhani; llza Mayuni (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2024)
Language and environment are related to one another. Languages affect how people perceive the world, how they behave, and how they interact with their local political, social, and ecological settings (Meighan, 2023). According to the new ideas, eco-literate students prepared to be an effective member of a sustainable society. ELT scholars and teachers must create, assess, and put into practice pedagogical techniques that promote ecological sustainability. However, no previous study has investigated implementations of Eco literacy in ELT in any systematic way. This review aimed to describe a general overview of implementations and opportunities of eco-literacy in ELT to help students facing Smart Society. Specific research studies were located using the predetermined criteria in Google Scholar databases, where the study was conducted. The outcomes include the following implementations, Eco-literacy benefits students in a smart society, requiring skill development and innovation, promoting creativity, encourages critical thinking about environmental issues and language use, fostering a shared understanding of alternative, attracting educators and curriculum developers interested in incorporating it into teaching materials.